SMART Ksafe / Noor Atika Ab Wahab, Noor Ammirah Md Uzir and Siti Rofilah Ismail - Ab Wahab, Noor Atika; Md Uzir, Noor Ammirah; Ismail, Siti Rofilah (2018)
Smart Kitchen Safe (KSafe) is the first time-lock container for food, gadgets, toys and other items user want. Thus, the product have been created as a simply place an item in the Kitchen Safe, close the lid, and set the timer. Once the timer is set, and the button is pressed, it will lock out. The safe remains locked and cannot be opened until the timer reaches zero and it can using the alarm to know the condition of container. The timer can hold until 10 days to keep the stuff safe. Hence, this container has other uses which are equipped with a button that can control the temperature condition of food either hot or cold.